Buzzard [videorecording (DVD)] - Potrykus, Joel; Potrykus, Joel; Burge, Joshua; Nelson, Teri Ann (Oscilloscope Laboratories, 2015)
Marty Jackitansky, a bored temp at a mortgage office, is out to get what he feels he deserves. He'll swindle and scam corporations out of ten dollars just for the thrill. Soon Marty hatches a scheme to steal petty refund checks from his mortgage company, thinking he'll somehow fool banks into cashing them. The third movie in the Animal Trilogy series following Coyote and Ape.